1991
DOI: 10.1021/ja00020a014
|View full text |Cite
|
Sign up to set email alerts
|

A molecular model for the major conformational substates in heme proteins

Abstract: 4. The holoazurin Trp 'Lb absorption band red shifts ca. 1 nm compared to apoazurin, while the 'Bb transition red shifts ca. 2 nm. The hydrophobicity of the Trp environment appears little changed between Cu(I) azurin, Cu(II) azurin, and apoazurin as evidenced by the narrowness of the Trp 'Lb 0-0 bands and from the Raman band shape for the Trp 1354-cm'1 band. The Trp 0-0 'Li, absorption spectral shifts most likely derive from subtle environmental changes, possibly alterations at sites somewhat distant from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 5 publications
(6 reference statements)
11
128
1
Order By: Relevance
“…These estimates are qualitative, but suggest that the contributions made by the distal histidine toward the free energy difference between the CO and O2 ligands are about 90% due to polar effects (electrostatic energy) and about 10% due to steric effects (van der Waals energy). This estimate, which suggests that the interaction between the bound ligands and the distal histidine is largely an electrostatic interaction, is consistent with the molecular model of Oldfield et al (1991). These workers presented a model of the major conformational substates of the COligated forms of several Hbs, Mbs, and peroxidases solely in terms of an electrical perturbation of the bound CO.…”
Section: Free Energy Resultssupporting
confidence: 76%
“…These estimates are qualitative, but suggest that the contributions made by the distal histidine toward the free energy difference between the CO and O2 ligands are about 90% due to polar effects (electrostatic energy) and about 10% due to steric effects (van der Waals energy). This estimate, which suggests that the interaction between the bound ligands and the distal histidine is largely an electrostatic interaction, is consistent with the molecular model of Oldfield et al (1991). These workers presented a model of the major conformational substates of the COligated forms of several Hbs, Mbs, and peroxidases solely in terms of an electrical perturbation of the bound CO.…”
Section: Free Energy Resultssupporting
confidence: 76%
“…1). Experiments, theory, and molecular dynamics simulations have shown that both the local and global coupling between protein structure and the CO vibrational transition frequency is mainly through the electric field along the CO bond (19,20,24,29,30,(35)(36)(37). The protein residues range from charged, to polar, to nonpolar.…”
Section: Resultsmentioning
confidence: 99%
“…The CϭO stretching frequency, (CϭO), appeared at 1969 cm Ϫ1 for natural abundance CO and at 1927 cm Ϫ1 for 13 CO. There is a well-known inverse correlation between the frequencies of the Fe-CO and CϭO stretching modes (15,(31)(32), which can be used to estimate the strength of the proximal ligand. The frequencies measured for CooA-CO lie on the line composed by heme proteins with neutral histidine as a proximal ligand (correlation plot not shown).…”
Section: Resultsmentioning
confidence: 99%